Prevalence of Anxiety and Depression in Young Patients Presenting with Atypical Chest Pain with Normal Coronaries - Adeel Ahmed; Sobia Mehreen; Naseer Ahmed Samore; Usman Iqbal; Muhammad Bilal Siddique; Mutahir Abbas Virk; Syed Khurram Shahzad; Abdul Hameed Siddiqui (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the prevalence of anxiety and depression in young patients presenting with atypical chest pain and normal coronary arteries.